2014
DOI: 10.1590/s0102-86502014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Alloxan diabetes alters the tensile strength, morphological and morphometric parameters of abdominal wall healing in rats

Abstract: PURPOSE:To investigate the effects of alloxan diabetes on the abdominal wall healing of rats undergoing laparotomy. METHODS:Ninety-six male Wistar rats weighing between 200 and 300 grams, divided into two groups: non-diabetic group (G1) and another with untreated diabetes (G2). Three months after diabetes induction, the animals underwent a 5cm-long-laparotomy and 5.0 nylon monofilament suture. After the surgery, 12 animals from each group were euthanized on days 4, 14, 21 and 30 corresponding to the moments M1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…This finding could potentially be explained by the observed increased risk of SSI, and is consistent with previously published studies by Sandy‐Hodgetts et.al and Riou et.al demonstrating that SSIs constitute a significant risk factor for wound dehiscence . Furthermore, animal data have previously demonstrated that wounds in diabetic rat models exhibit decreased tensile strength, collagen density, and wound contraction, which could also explain the association between diabetes and wound dehiscence observed in our study …”
Section: Discussionsupporting
confidence: 94%
“…This finding could potentially be explained by the observed increased risk of SSI, and is consistent with previously published studies by Sandy‐Hodgetts et.al and Riou et.al demonstrating that SSIs constitute a significant risk factor for wound dehiscence . Furthermore, animal data have previously demonstrated that wounds in diabetic rat models exhibit decreased tensile strength, collagen density, and wound contraction, which could also explain the association between diabetes and wound dehiscence observed in our study …”
Section: Discussionsupporting
confidence: 94%
“…Our study also revealed increased rates of wound dehiscence in diabetic patients ( P = .01). Animal data from wounds in diabetic rats have been shown to exhibit decreased tensile strength, collagen density, and contraction (Minossi et al, ). Furthermore, wound infection is a common risk factor for dehiscence (Sandy‐Hodgetts, Carville, & Leslie, ), which might contribute to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced scar collagen formation and tensile strength have also been observed in mice lacking a11b1 integrin 41 and in diabetic rats, in which these abnormalities lead to higher incidence of dehiscence. 42 Of interest, reduced collagen deposition is not necessarily coupled with decreased tensile strength, because the opposite has been shown with poly-N-acetyl-glucosamine nanofiber treatment 43 or with the use of a selective adenosine A2AR-antagonist. 44 In both cases, reduced scar collagen content was seen with concomitantly increased tensile strength.…”
Section: Discussionmentioning
confidence: 99%